Perkembangan Perkembangan Demokrasi Indonesia Pasca Reformasi 1998 Dalam Lingkup Hubungan Warga Negara Dengan Negara Dalam Presfektif Hukum : Perkembangan dan situasi demokrasi indonesia pasca reformasi, Peran negara dalam pemenuhan demokrasi, Kemunduran dan permasalahan baru yang muncul dalam demokrasi pasca reformasi - Yadi Supriyadi Supriyadi; Dhila Fadliah; Taufik Imam Hidayat; Humaysi Camila Hilda Elzen; Nathania Tiara Putri (Fakultas Keguruan dan Ilmu Pendidikan Program Studi Pendidikan Pancasila dan Kewarganegaraan, 2025)
The 1998 reformation became a starting point in the history of Indonesian democracy, the pattern of the relationship between the state and citizens also changed to become more democratic, the government system that was originally dictatorial was slightly more democratic. This journal aims to analyze the development of Indonesian democracy after the reformation, focusing on the scope of the relationship between the state and citizens from a legal perspective. It examines how the state fulfills its democratic obligations to its citizens, as well as how citizens exercise their democratic rights, including voting rights, freedom of expression, and the right to participate in political decisionmaking. In addition, it explores the progress and challenges facing Indonesia's post-reform democracy, such as the emergence of new issues in the implementation of democratic rights and the often hindered enforcement of the law. By analyzing relevant legal and statistical data, it also discusses the important role of law in maintaining a balance between the state's right to govern and the individual rights of citizens to participate freely. This journal is expected to provide insight into the extent to which the implementation of democratic principles in Indonesia is in line with the development of law and the fulfillment of human rights, and provide recommendations for the improvement of Indonesian democracy in the future.